Principalsâ€™ Instructional Leadership towards Teachers’ Self-Efficacy - Isa Medina Machmudi Isa, Nitce; Norhaini Mansor, Azlin; Lail Abdul Wahab, Jamalul; Salwana Alias, Bity (International Journal of Engineering and Technology, 2018)
Principalsâ€™ instructional leadership practices have proved to be an imperative predictor to teachersâ€™ self-efficacy. Yet, educators are concerned about the ability to adapt to new instructional leaderships due to unspoken principal-teacher expectations. This paper discusses the extent of instructional leadership practices by two newly transferred principals at two different schools. The purpose of this quantitative study was to examine how their instructional leadership practices affected the self-efficacy of the teachers. Through the use of a cross-sectional survey, responses made by 64 teachers employed in one public school and one privately-run school, were compared. The Principal Instructional Management Rating Scale (PIMRS) Teacher Short Form and the Teachersâ€™ Sense of Efficacy Scale (TSES) were used for data collection. The findings showed a high level of instructional leadership practices and self-efficacy in both schools. The test results indicated a strong and positive relationship between the principalsâ€™ perceived instructional leadership practices and the teachersâ€™ self-efficacy. Some of the details even suggested that newly transferred principals enforce specific school goals as their main agenda. Nevertheless, the areas of significance identified by this study may help district school superintendents develop the right knowledge to support newly transferred principals in their instructional leadership, thus enhancing teachersâ€™ self-efficacy at the school level.Â Â